Optimalisasi Kualitas Tesis Mahasiswa Magister Manajemen Administrasi Rumah Sakit (MARS) melalui Pendekatan Strategi Pengajaran pada Mata Kuliah Metodologi Penelitian - Dr.,M.Ed, Johanes (Lembaga Penerbitan Universitas Esa Unggul, 2024)
Abstract:Improving the quality of master's students' theses in hospital administration management (MARS) is an essential aspect in supporting the development of quality scholarly and practical healthcare management. This article discusses teaching strategies in research methodology as an effort to enhance the quality of master's students' theses in hospital administration management. By implementing effective teaching strategies, students can gain a profound understanding of research methodology relevant to the context of hospital administration. A holistic and interactive approach to teaching can encourage students to develop critical and analytical research skills, as well as strengthen their abilities in designing and conducting high-quality research. Through this approach, it is hoped that students will be able to produce theses that make significant contributions to enriching insights and practices in hospital administration management. The implications of this article underscore the importance of teaching roles focused on developing research methodology skills in enhancing the quality of academic outputs for master's students in hospital administration management. Thus, this article contributes to the context of developing high-quality healthcare education relevant to practical demands in the field.Keyword: Optimalization Thesis. Teaching Strategies, Research Methodology